2004
DOI: 10.1080/15459620490432150
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and Associated Reactions to Mineral Dusts: Sodium Borate, Calcium Oxide, and Calcium Sulfate

Abstract: Occupational exposure limits (OELs) for irritant dusts have had no quantifiable bases. This study (1) charted chemosensory feel, denoted chemesthesis here, to dusts of calcium oxide (1 to 5 mg/m(3)), sodium tetraborate pentahydrate [sodium borate] (5 to 40 mg/m(3)), and calcium sulfate (10 to 40 mg/m(3)); (2) examined correlates of the chemesthetic sensations; and (3) sought to illuminate the basis for potency. Twelve screened men exercised against a light load while they breathed air in a dome fed with contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 18 publications
2
29
0
3
Order By: Relevance
“…The Cain et al (2004 studies were selected over the Wegman et al (1991Wegman et al ( , 1994 studies as the basis of the acute-duration inhalation MRL for boron because they identified a NOAEL based on observations from carefully-controlled exposures of volunteers. The Wegman et al (1991Wegman et al ( , 1994 data are problematic for identifying a NOAEL or LOAEL because the average irritation intensity level reported prior to a work shift was very close to the average intensity level reported for all incidents of nasal irritation.…”
Section: Inhalation Mrlsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cain et al (2004 studies were selected over the Wegman et al (1991Wegman et al ( , 1994 studies as the basis of the acute-duration inhalation MRL for boron because they identified a NOAEL based on observations from carefully-controlled exposures of volunteers. The Wegman et al (1991Wegman et al ( , 1994 data are problematic for identifying a NOAEL or LOAEL because the average irritation intensity level reported prior to a work shift was very close to the average intensity level reported for all incidents of nasal irritation.…”
Section: Inhalation Mrlsmentioning
confidence: 99%
“…Further, the best 0.25-hour TWA data (confirmed by worker response and simultaneous air sampling by a study technician) suggest that the probability of workers reporting incidences of nasal irritation occurred when estimated boron concentrations reached 0.8-1.2 mg boron/m 3 , which is very similar to the laboratory findings of Cain et al ( , 2008. Cain et al (2004 trained male and female volunteers to recognize the difference in chemesthetic feel (pungency or irritancy) of various levels of CO 2 offered to the eyes, nose, and throat. Exposures of ≥17.7% CO 2 resulted in a "feel" described by the volunteers as irritating.…”
Section: Inhalation Mrlsmentioning
confidence: 99%
“…In zwei experimentellen Studien (Cain et al 2004(Cain et al , 2008 (Wise und Wysocki 2002). Eindeutige Dosis-Wirkungs-Beziehungen konnten in dieser Studie nicht ermittelt werden, da ähnliche Intensitätsangaben für 10 und 40 mg Dinatriumtetraborat-Pentahydrat/m 3 gemacht wurden (Cain et al 2004).…”
Section: Inhalativunclassified
“…Eindeutige Dosis-Wirkungs-Beziehungen konnten in dieser Studie nicht ermittelt werden, da ähnliche Intensitätsangaben für 10 und 40 mg Dinatriumtetraborat-Pentahydrat/m 3 gemacht wurden (Cain et al 2004). Basierend auf den physiologischen Messungen kann für Dinatriumtetraborat-Pentahydrat eine NOAEC von 5 mg/m 3 abgeleitet werden.…”
Section: Inhalativunclassified
See 1 more Smart Citation